Upaya Penurunan Kasus TB Paru di Wilayah Kerja Puskesmas Kresek Kecamatan Kresek, Kabupaten Tangerang, Provinsi Banten - Sanjaya, Juliana; Drew, Clement (Syntax Literate, 2025)
data at the Kresek Community Health Center, the number of tuberculosis cases increased from January to May. Seeing this, it is necessary to carry out a community diagnosis approach to further analyze and identify the factors causing the increase in cases of pulmonary tuberculosis so that immediate intervention can be carried out to prevent the spread and reduce the number of new cases of pulmonary tuberculosis in the working area of the Kresek Community Health Center, Tangerang Regency. Objective: To enhance public awareness of TB, proper coughing, and handwashing within the Kresek Community Health Center’s operational area. Method: Utilizing the Blum Paradigm for community diagnosis to identify underlying causes, conducting mini-seurveys to gather data, the non-scoring Delphi method to prioritize problem, and fishbone diagrams to determine root causes of issues. Interventions include education on TB, cough etique and handwashing steps. Intervention is monitored using the Plan-Do-Check-Action (PDCA) cycle, along with systemic approach to evaluation. Results: Lifestyle factors was contributing to hig TB cases according to the Blum Paradigm. Intervention I (Pulmonary TB) outcomes indicate 29 participants (80,5%) experienced an improvement in post-test score compared to pre-test, wiht 32 participants (88,9%) achieving a post-test score ≥70. Intervention II (PHBS) outcomes indicate 34 participant (94,4%) showed an improvement in post-test score compared to pre-test, and 35 participants (97,2%) achieved a post-test score ≥70 and 6 randomly selected participants executed all two demonstration. Conclusion: There has been an improvement in knowledge regarding pulmonary TB, cough etiquette, and handwashing steps in the working area of Kresek Community Health Center.